Emerging concepts regarding pro- and anti tumor properties of B cells in tumor immunity - Qin, You; Lu, Furong; Lyu, Kexing; Chang, Alfred E.; Li, Qiao (Frontiers in Immunology, 2022)
Controversial views regarding the roles of B cells in tumor immunity have existed for several decades. However, more recent studies have focused on its positive properties in antitumor immunity. Many studies have demonstrated a close association of the higher density of intratumoral B cells with favorable outcomes in cancer patients. B cells can interact with T cells as well as follicular dendritic cells within tertiary lymphoid structures, where they undergo a series of biological events, including clonal expansion, somatic hypermutation, class switching, and tumor-specific antibody production, which may trigger antitumor humoral responses. After activation, B cells can function as effector cells via direct tumor-killing, antigen-presenting activity, and production of tumor-specific antibodies. At the other extreme, B cells can obtain inhibitory functions by relevant stimuli, converting to regulatory B cells, which serve as an immunosuppressive arm to tumor immunity. Here we summarize our current understanding of the bipolar properties of B cells within the tumor immune microenvironment and propose potential B cell-based immunotherapeutic strategies, which may help promote cancer immunotherapy.